Bridging the motivational gap: Indonesian university students’ reading habits and interest in culturally-grounded extensive reading materials - Stella Prancisca (Englisia: Journal of Language, Education, and Humanities, 2026)
Indonesian students' persistently low performance in international literacy assessments, including the Programme for International Student Assessment (PISA), underscores a critical need to reevaluate pedagogical approaches to English as a Foreign Language (EFL) reading instruction. Recent scholarship advocates for the implementation of Extensive Reading (ER) programs, which enable students to read at their own level, pace, and interest, thereby gradually fostering sustainable reading habits. While conventional ER materials have predominantly been developed using Western-based narratives and cultural contexts, the integration of local stories is necessary to further enhance student engagement. This study identifies students' reading habits in both Indonesian and English as a foundation for developing ER materials, with particular emphasis on exploring student perceptions of reading materials infused with local values. Employing a survey design, the study involved 104 university students in West Kalimantan. A questionnaire was administered to examine reading frequency, types of reading materials, language preferences, as well as attitudes toward and interest in local reading materials. The findings reveal a motivational dichotomy: reading in Indonesian is driven primarily by intrinsic motives, whereas reading in English is dominated by extrinsic motives. The low frequency of English reading is further compounded by linguistic challenges, including lengthy and complex sentence structures as well as difficult vocabulary. Nevertheless, students demonstrated a notably strong interest in English reading materials based on Pontianak culture, believing that local content facilitates English comprehension. These findings affirm that the development of culturally grounded extensive reading materials constitutes a strategic, evidence-based intervention capable of bridging motivational and linguistic gaps, fostering sustainable reading habits, and enhancing long-term English competence.